(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the scientific community, review articles provide an overview of a particular field. Youth involvement in Assam’s tea gardens and their contribution to sustainable development is explored in this review article. The paper examines society, the environment, and culture of tea gardens from the point of view of young people. Environmental conservation, social development, and economic empowerment are highlighted in the article. It focuses on youth’s role in supporting sustainable agriculture, community development, and overall well-being within tea gardens. A systematic review of existing literature identifies key success factors, challenges, and gaps in the involvement of tea garden youth in sustainable development. Youth engagement in the tea industry, local communities, and regional sustainable development goals are explored. Additionally, the article provides recommendations for policymakers, stakeholders, and tea garden managers. Tea garden youth need targeted interventions, capacity building, education, and empowerment programs to ensure a sustainable future. Ultimately, this article seeks to provide an in-depth analysis of tea garden youth in Assam’s sustainable development. It aims to inspire further research and action by synthesizing existing research and identifying key areas for improvement.